RESPON PERTUMBUHAN TUNAS SANINTEN (Castanopsis argentea (Blume) A.DC.) TERHADAP PEMBERIAN ZAT PENGATUR TUMBUH BAP DAN IAA SECARA IN VITRO The growth response of Saninten (Castanopsis argentea (Blume) A.DC.) In Vitro by Adding Plant Growth Regulator BAP - Arum Sekar Wulandari; Erina Sulistiani; Esthi Liani Agustiani (Jurnal Silvikultur Tropika, 2017)
Saninten (Castanopsis argentea (Blume) A.DC.) is one of the member Fagaceae family which can produce wood and non-wood product. Micropropagation of saninten by in vitro has never been reported. This research aims to identify the growth response of saninten shoot by adding Plant Growth Regulator (PGR), they are 6-benzylaminopurine (BAP) and indole-3-acetic-acid (IAA) with different concentrations in propagation in vitro on woody plant medium (WPM). The research conducted a completely randomized design (CRD) factorial. They are PGR type and PGR concentration. The PGR type consist of two levels namely BAP and IAA. PGR concentration consist of three levels namely 0 mg/L BAP and IAA, 0.5 mg/L BAP or 0.1 mg/L IAA, and 1.0 mg/L BAP or 0.1 mg/L IAA. Parameters observed is the amount of shoot, shoot height, and callus growth. The combination of BAP (0, 0.5, 1 mg/L) and IAA (0, 0.1, 0.1 mg/L) haven’t produce optimal growth of shoot. WPM medium with 0.5 mg/L BAP was able to produce the best of percentage of shoot, the number of shoots, and shoot height growth. WPM medium with IAA concentration of 0.1 and 0.2 mg/L produce explant with callus.Key words: 6-benzylaminopurine (BAP), Castanopsis argentea, indole-3-acetic-acid (IAA), woody plant medium (WPM)